2020
DOI: 10.21203/rs.3.rs-40688/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the contribution of assisted reproduction methods for the future development of the number of live births in Czechia

Abstract: Abstract Background: The key demographic trend concerns the postponement of parenthood to later ages. Moreover, the number of Czech women of reproductive age is decreasing, which will lead to a decrease in the number of live births even with higher fertility. The aims are to assess recent trends concerning using ART in Czechia and to estimate the impact of using ART on the future development of the number of live births. Methods: Based on data on the number of ART cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous research in Europe and the United States has mostly focused on the impact of ART on overall fertility by adopting either a period (Habbema et al, 2009;Hoorens et al, 2007;Tierney, 2022) or cohort (Leridon, 2017;Leridon & Slama, 2008;Sobotka et al, 2008) approach, with most studies showing a rather modest contribution of 2-5%. Studies that have looked at age-specific ART fertility have found that the absolute contribution of ART to the TFR often peaks in the mid-30s, while the relative share of ART births increases with age (Burcin et al, 2020;Lazzari et al, 2021;Tierney, 2022). For example, Lazzari et al, (2021) found that increases in period fertility rates at late (40 +) reproductive ages in Australia were largely driven by the increasing use of ART.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in Europe and the United States has mostly focused on the impact of ART on overall fertility by adopting either a period (Habbema et al, 2009;Hoorens et al, 2007;Tierney, 2022) or cohort (Leridon, 2017;Leridon & Slama, 2008;Sobotka et al, 2008) approach, with most studies showing a rather modest contribution of 2-5%. Studies that have looked at age-specific ART fertility have found that the absolute contribution of ART to the TFR often peaks in the mid-30s, while the relative share of ART births increases with age (Burcin et al, 2020;Lazzari et al, 2021;Tierney, 2022). For example, Lazzari et al, (2021) found that increases in period fertility rates at late (40 +) reproductive ages in Australia were largely driven by the increasing use of ART.…”
Section: Introductionmentioning
confidence: 99%